EDUKASI TENTANG WABAH DAN PENCEGAHAN PENYAKIT LELE KUNING DI KELOMPOK PEMBUDIDAYA IKAN KARYA MINA LELE KECAMATAN MUNCAR, KABUPATEN BANYUWANGI, JAWA TIMUR - Maria Agustina Pardede; Prayogo Prayogo; Dwi Retna Kumalaningrum; Mohhamad Faizal Ulkhaq; Dewi Ambarwati; Mohammad Hilmy Maulana; Shierly Zaissiliya Clarissa; Yunita Ika Putri Puspitasari; Farhan Gymnastiar Baihaqi; Nirmala Sagita; Octaviano Ramadhan (Universitas Mataram, 2026)
Catfish (Clarias sp.) is a major freshwater aquaculture commodity with high production value in Indonesia. Intensification using Recirculating Aquaculture Systems (RAS) has increased disease risks, including jaundice, which is associated with high mortality rates. Jaundice in fish is generally linked to impaired liver function and disruption of bilirubin metabolism, leading to abnormal pigment accumulation and yellow discoloration. Limited farmer knowledge and improper management practices further exacerbate disease outbreaks and production losses. This activity aimed to improve farmers’ understanding of the causes, early detection, and prevention of jaundice disease to enhance fish health and aquaculture productivity. The program was conducted through systematic counseling, training on early detection and field diagnosis, and practical implementation of sanitation, water quality management, biosecurity, and fish quarantine. Evaluation was performed using pre-test, post-test, and regular monitoring of culture conditions. The results demonstrated a substantial improvement in farmers’ knowledge and skills in recognizing clinical symptoms and conducting early disease detection. The application of sanitation and biosecurity measures improved water quality and reduced environmental risk factors. Most ponds showed a decrease in disease outbreaks and mortality rates. Fish survival rates increased compared to pre-intervention conditions, indicating the effectiveness of the implemented strategies. Additionally, farmers became more capable of independently applying fish health management practices, including feed management, water quality control, and preventive measures against disease transmission. This program effectively enhanced farmers’ capacity in preventing jaundice, contributing to improved fish health and aquaculture productivity.